Oral Presentations as Catalysts for Critical Thinking: Indonesian EFL Students’ Perceptions - Hamzah Puadi Ilyas; Istaryatiningtias Istaryatiningtias (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
Critical thinking is a core competency in higher education, especially in EFL contexts where students must engage both linguistically and cognitively. This study investigates how oral presentations function as catalysts for critical thinking among Indonesian EFL undergraduates. Guided by an interpretive phenomenological approach, data were collected from 13 English education majors through reflective journals and semi-structured interviews and analyzed using Braun and Clarke’s thematic framework. One salient finding shows that students strengthened analytical reasoning and reflective judgment through both individual and collaborative presentation practices. Four themes emerged: presentations triggered analytical reasoning, fostered reflective learning, enhanced confidence, and revealed contrasts between individual and group tasks. These findings illustrate that oral presentations provided authentic opportunities for students to analyze information, evaluate arguments, and engage in collaborative reasoning. The study thus offers empirical evidence that classroom presentations can foster sustained cognitive engagement when accompanied by structured reflection. The study demonstrates that oral presentation tasks can effectively promote students’ intellectual engagement, and it contributes to EFL pedagogy by underscoring the role of reflection, scaffolding, and balanced task design in enhancing critical thinking within oral presentation courses. It suggests that incorporating structured reflection and guided feedback into public speaking classes can strengthen both linguistic performance and cognitive growth.